Bioreduction of hexavalent molybdenum to molybdenum blue using Serratia sp. MIE2 and purification of molybdenum-reducing enzyme - Halmi, Mohd Izuan Effendi (2014)
Molybdenum reduction is an old phenomenon that has received very low attention compare to other well-known and extensively studied metals such as chromium, mercury and lead. Molybdenum has long been known to be toxic to ruminants and not toxic to other organisms. However, more recently it has been increasingly reported that molybdenum shows toxic effects to reproductive organs of fish, mouse and even humans at concentrations between 1 and 100 ppm. Hence its removal from the environment is highly sought after. The isolation of molybdenum reducing bacteria and the elucidation of the reducing mechanism will lead to an efficient bioremediation system. To fulfil this, a new Mo-reducing bacterium was isolated from an agriculture soil plot from Universiti Putra Malaysia. The isolate was tentatively identified as Serratia sp. MIE2 based on 16s rDNA molecular phylogeny. Serratia sp. MIE2 is a gram negative, oxidase and catalase positive bacterium. The molybdenum blue produced by Serratia sp. MIE2 exhibited a unique absorption spectrum with maximum peak at 865 nm and a shoulder at 700 nm. Dialysis tubing experiment showed that molybdate reduction by Serratia sp. MIE2 was an enzymatic process and not chemically mediated. Characterization and optimization of molybdenum blue production by Serratia sp. MIE2 was carried out using one factor at a time (OFAT) and Response Surface Methodology (RSM). One factor at a time (OFAT) showed the optimum conditions supporting molybdate reduction occurred at pH 6.0, from 27 to 35 oC and 30-40 g/L sucrose as the carbon source or electron donor. The best nitrogen source was ammonium sulphate with an optimum concentration at 10 g/L. Moreover, the optimum concentrations of phosphate and molybdate were 2 and 10 mM,respectively. Molybdate reduction was maximized and optimized using response surface methodology (RSM) with optimum conditions occuring at 20 mM of molybdate, 25 g/L of sucrose, pH 6.25 and 3.95 mM of phosphate with molybdenum blue production increasing from an OFAT absorbance yield of 10.0 to higher than 20.0 as measured at 865 nm. Modelling kinetic studies of Serratia sp. MIE2 using the optimum conditions obtained from the classical method (OFAT) show that the best model was Teissier followed by Luong, Aiba, Yano and Haldane with correlation coefficient, R2 values of 0.994, 0.993, 0.992, 0.990 and 0.982, respectively. The calculated values of Pmax, Ks and Ki of the best model were 0.89 μmole Molybdenum blue per hour, 5.84 mM and 32.23 mM respectively. Otherwise, modelling kinetics using the optimum condition obtained from RSM showed that the Luong model was the best model followed by Teissier, Aiba, Yano and Haldane with correlation coefficient, R2 values of 0.999, 0.994, 0.993, 0.992 and 0.965, respectively. However, since Luong exhibited 4 kinetic constants while Teissier has only 3 constants, by default, Teissier model was chosen due to its mathematical simplicity. The calculated values of R2,Pmax, Ks and Ki of the best model, Teissier were 1.97 μmole Mo-blue per hour, 5.79 mM and 31.48 mM, respectively. Modelling kinetics showed the value of Pmax was increasing from 0.89 μmole Molybdenum blue per hour to 1.97 μmole molybdenum blue per hour indicating that molybdate reduction yield increase several fold after optimization using RSM. Before purification process, preliminary studies such as effect of storage and chromatographic stabilities, effects of restorative and inhibitive agents were carried out to minimise denaturation and to maximise yield of purified enzyme. The buffer use during storage and purification process was Tris-HCl at pH 7.0. Mo-reducing enzyme was stable when stored at -80oC for both 24 hours and one month followed by storage on ice (0oC). Temperature stability study showed that the enzyme was most stable at 25oC followed by 40oC with complete lost of activity at 60 and 40 minutes of incubation at 54 and 70oC. EGTA or (ethylene glycol tetraacetic acid), EDTA, Triton X-100, DBS and SDS decrease 50% activity of enzyme at concentration 0.1mM, 0.1mM, 0.1%, 0.1%, and 0.1%, respectively. DTT could restore the Mo-reducing enzyme activity of up to 100% at the maximum concentration of 5 mM for DTT and 0.5 mM for O-mercaptoethanol. Effects of cofactor suggest that nickel might be an important cofactor for the enzyme. Heavy metals such as mercury and zinc effect strongly inhibited the Mo-reducing enzyme. The coenzyme such as FMN and FAD were able to restore Mo-reducing enzyme activity. Mo-reducing enzyme was not inhibited by respiratory inhibitors, therefore,the electron transport chain of this bacterium is not the site of molybdate reduction. Purification of the Mo-reducing enzyme was done using ammonium sulphate precipitation, gel filtration on Zorbax GF-250 and Zorbax GF-450 with a 20.8 purification fold. The molecular mass was estimated to be 100 kDa by SDSpolyacrylamide gel electrophoresis and the enzyme was monomeric. Mo-reducing enzyme showed maximum activity at 35oC and pH 5. The enzyme was assayed using NADH as the electron donor with the maximum initial velocity, Vmax of 16.18 nmole molybdenum blue/min/mg protein and a Michaelis constant, Km at 0.89 mM. The optimum concentration of phosphomolybdate (electron acceptor substrate) was 10 mM, with a Vmax of 6.89 nmole molybdenum blue/min/mg protein (NADH as electron donor at saturated concentrations) and Km of 6.02 mM. Identification of pure enzyme using MALDI-TOF showed only peptide DNAATRSEAMSLIHGR shows similarity to 35% to nitrile oxidoreductase and GTP cyclohydrolase I. The low similarity value prohibited further analysis to be carried out. Thus, the enzyme is assigned as hypothetical protein.